INVOLVEMENT OF NITRIC OXIDE IN THE ADAPTOGENIC EFFECT OF BACOPA MONNIERA (BRAHMI) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Bacopa monniera (BM) is an Ayurvedic medicine, used for centuries as nootropoic, anxiolytic, antidepressant, analgesic, antipyretic, antiepileptic agent and adaptogen. Adaptogens are drugs that promote non-specific resistance of the body and recognized as useful anti-stress agents. Although, the adaptogenic effect of BM is well documented, its mechanism is still not well defined. Stress is known to increase nitric oxide (NO) level in brain tissues, moreover, BM reported to inhibit iNOS expression in vitro. Hence, the present investigation was designed to evaluate the involvement of NO in adaptogenic effect of BM. Mice were exposed to overnight audiogenic stress from day 1 to 10. Various drugs treatments were given before the exposure on each day. Effects of stress were assessed interms of anxiety by social interaction and depression by forced swim test. Results showed that exposure to audiogenic stress significantly induced anxiety and depression on day 1 and 4, whereas, no difference after day 7 and 10, indicated adaptation to stress. Administration of BM (40 and 80 mg/kg, p.o.) attenuated the effect of audiogenic stress and facilitated the adaptation to stress. L-arginine impaired the adaptation to stress. In addition, concomitant administration of BM and L-NAME or 7-NI produced synergistic effect in audiogenic stress mice. Moreover, BM attenuated the effects of L-arginine. Further, BM administration significantly decreased audiogenic stress-induced increased NOx levels in cortex, hypothalamus and hippocampus. Thus, BM has significant adaptogenic activity and this effect is probably medicated through nitrergic system.